Alkyl Nitrites: Novel Reagents for One-Pot Synthesis of 3,5-Disubstituted Isoxazoles from Aldoximes and Alkynes - Kadam, Kishorkumar S.; Gandhi, Thirumanavelan; Gupte, Amol; Gangopadhyay, A. K.; Sharma, Rajiv (Synthesis, 2016)
An efficient, one-pot approach has been described for the synthesis of 3,5-disubstituted isoxazoles from substituted aldoximes (mixture of E and Z) and alkynes, using alkyl nitrites under conventional heating conditions. The key nitrile oxide intermediates that are required for the synthesis of isoxazoles are formed by treatment of substituted aldoxime with either tert-butyl nitrite or isoamyl nitrite. The generated nitrile oxides underwent in situ [3+2] dipolar cycloaddition to the substituted alkynes to give 3,5-disubstituted isoxazoles regioselectively in high to excellent yields. The developed synthetic methodology was applied for the synthesis of a previously reported potent hDGAT1 inhibitor.
Keywords: isoxazoles; nitrile oxides; aldoximes; tert-butyl nitrite; isoamyl nitrite